2020
DOI: 10.1186/s40594-020-00245-0
|View full text |Cite
|
Sign up to set email alerts
|

Understanding intrinsic challenges to STEM instructional practices for Chinese teachers based on their beliefs and knowledge base

Abstract: Background China has great student participation in STEM education. Chinese society has a progressive and positive attitude towards STEM as it is considered to provide more opportunities in life. Teachers play a vital role in the success of any STEM program in K-12 schools. However, teachers are facing instructional challenges because of the interdisciplinary nature of the STEM curriculum and the current typical school structure. The success of the STEM programs depends on teachers’ beliefs and their knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 49 publications
5
52
1
Order By: Relevance
“…Theoretically, it provides new insight into STEM educational implementation. Different from previous studies that focus only on the roles of teachers' knowledge, skills, self-efficacy, and attitude in STEM educational implementation in primary and secondary schools [4,5,10,13,38], the study suggests that teachers' emotions are also an important factor influencing the outcome of STEM education since they significantly shape teachers' motivation, commitment, and engagement in STEM educational work. From the social constructionist perspective, the study advances our theoretical understanding of how teachers' positive emotions toward STEM educational work may be constructed by their interpretations of the work and sustained by enabling school institutions.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Theoretically, it provides new insight into STEM educational implementation. Different from previous studies that focus only on the roles of teachers' knowledge, skills, self-efficacy, and attitude in STEM educational implementation in primary and secondary schools [4,5,10,13,38], the study suggests that teachers' emotions are also an important factor influencing the outcome of STEM education since they significantly shape teachers' motivation, commitment, and engagement in STEM educational work. From the social constructionist perspective, the study advances our theoretical understanding of how teachers' positive emotions toward STEM educational work may be constructed by their interpretations of the work and sustained by enabling school institutions.…”
Section: Discussioncontrasting
confidence: 83%
“…A similar situation is found in Chinese societies [8]. Dong et al [13] found that teachers in China face pedagogical and instructional challenges in implementing STEM education because of the limited knowledge and beliefs of STEM education. Geng et al [14] noted that Hong Kong teachers tend to have a weak sense of self-efficacy belief in STEM education since they receive insufficient training, causing them to lack understanding and the skills of teaching, organizing, and managing STEM activities.…”
Section: Introductionsupporting
confidence: 60%
“…It is encouraging to observe the positive attitudes that the participants in this study exhibit towards integrated STEM education and the fact that they seem to have been positively influenced by their postgraduate studies. Teachers' attitudes to integrated STEM education are directly predictive of their subsequent instructional practices (Dong et al, 2020) so it is clear that PD initiatives that can enhance teachers' attitudes will have a positive impact on the implementation of integrated STEM approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Many STEM teachers reported that they suffered high pressure or other negative emotions under these reform initiatives (Zhang & Sun, 2018). STEM teachers are encountering various difficulties and challenges in meeting the requirements of this reform when they play roles as school-based STEM curriculum developers, active implementers of innovative STEM teaching practices, and facilitators of students' STEM learning (Dong et al, 2020). Put simply, it has been increasingly recognized that the job of a STEM teacher in China is challenging.…”
Section: Contextmentioning
confidence: 99%